An effect of environmental disclosure on financial performance of manufacturing companies in Indonesia and Singapore - Cahyawati, Noor Endah; Azizah, Almas (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2024)
This study aimed to analyze the effect of environmental disclosure on the financial performance of manufacturing companies in Indonesia and Singapore. The sample in this study consisted of 108 manufacturing companies from Indonesia and 102 manufacturing companies from Singapore. The data analysis technique used simple linear regression. The results of this study indicated that environmental disclosure affected financial performance (ROA, ROE, and NPM) in Indonesia. However, the research on the effect of Corporate Social Responsibility (CSR) on financial performance (ROA, ROE, and NPM) in Singapore showed the opposite results. Furthermore, the results of this study also showed that environmental disclosure did not affect EPS in Indonesia and Singapore. In addition, this study also proved that Indonesia and Singapore had different levels of CSR implementation in which Singapore had a better quality of CSR disclosure than Indonesia. Hopefully, the study can provide an overview of the non-monetary aspects that should be considered in investment.